ANALISIS PERISTIWA STOCK SPLIT TERHADAP HARGA SAHAM, LIKUIDITAS SAHAM DAN ABNORMAL RETURN ( STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015) - Satria, Kesuma; Adnan, Adnan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of this research is to analyze the impact of stock split events upon stock price, stock liquidity and abnormal return in manufacturing company which registered at Indonesia Stock Exchange from 2011 until 2015. The type of data used in this research is secondary data which obtained from financial statements publishing by capital market reference center that existed in Indonesia Stock Exchange. The sample used in this research is study case with the total of the population is 127 companies. Method used in this research is purposive sampling which yielded 18 companies sample. Meanwhile, the examination of hypothesis used is event study method. The result of this research illustrate that stock split events did not give an impact upon stock price, stock liquidity and abnormal return simultaneously. However, in case of considering each variable, there is a difference